2018
DOI: 10.15244/pjoes/79438
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Variations of Trophic Status of a Small Lowland River

Abstract: The circulation of water and chemical components in rural landscapes has been seriously disrupted in recent decades as a result of growing civilization, including intensification of agriculture, the application of mineral fertilizers, chemical weed and pest control, high concentrations of livestock, and mistakes in agricultural techniques. All of this has caused an increasing rate of eutrophication followed by changes in aquatic ecosystems. Assessing the trophic status of rivers is less effective when only che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…While selecting the number of main components, it was supported by incorporating the main components prior to a definite breakage of the Scree plot (Fig. 4) [43][44][45]. We concluded that four main components can represent the data of Tuzaklı Pond (Table 5).…”
Section: mentioning
confidence: 79%
“…While selecting the number of main components, it was supported by incorporating the main components prior to a definite breakage of the Scree plot (Fig. 4) [43][44][45]. We concluded that four main components can represent the data of Tuzaklı Pond (Table 5).…”
Section: mentioning
confidence: 79%
“…The Vaucheria genus colonizes all types of freshwater habitats. These xanthophytes share the same ecological profile as Cladophora genus, with the exception of a few environmental conditions, in particular, sunlight (Staniszewski et al, 2019; Weekes et al, 2014). They prefer shady habitats with depths of up to 70 cm (Ensminger et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of agricultural operations prevents accurate and precise identification of the number of sources and volumes of pollutant emissions ( Moss, 2008 ), thus formulating of precise conclusions is difficult. They can be formulate predominantly for small subcatchments with similar land use structure and lack of major point sources of pollution ( Staniszewski et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%